The Implementation of The Problem Based Learning Model With Wordwall Application on The Mathematics Learning Motivation of Grade 3 Students of Trosemi 02 State Elementary School - Monica Novitasari; Achmad Fathoni (FKIP - Universitas Riau, 2026)
Education plays an essential role in shaping students’ intellectual abilities, character, and overall potential, enabling them to adapt to the demands of a rapidly changing world. However, learning motivation in mathematics remains a persistent challenge, particularly when instructional practices rely heavily on abstract explanations and limited media variation. This study investigates the effectiveness of integrating the Problem-Based Learning (PBL) model with the digital platform Wordwall to enhance third-grade students’ motivation in learning mathematics at SDN Trosemi 02. Using a quantitative approach with a one-group pretest–posttest design, the research involved 14 students who received treatment through contextual problem-solving activities supported by interactive game-based media. Data were collected through questionnaires, tests, observations, and documentation, and analyzed using validity, reliability, normality tests, and a paired sample t-test. The findings reveal significant improvements in both learning outcomes and motivation, supported by a Sig. value of 0.000 (< 0.05). Students showed increased enthusiasm, participation, and confidence after the intervention. The combination of PBL and Wordwall provided a more engaging, meaningful, and student-centered learning experience. These results indicate that integrating contextual learning models with digital media can effectively strengthen learning motivation and support improved mathematical understanding.